Cover Feature: Excitation Energy Transfer and Exchange‐Mediated Quartet State Formation in Porphyrin‐Trityl Systems (Chem. Eur. J. 8/2021). Issue 8 (7th December 2020) - Nolden, Oliver; Fleck, Nico; Lorenzo, Emmaline R.; Wasielewski, Michael R.; Schiemann, Olav; Gilch, Peter; Richert, Sabine
Abstract : The photo‐induced formation of a quartet state in a molecular conjugate consisting of a porphyrin and a trityl moiety is depicted in the cover image. Such photogenerated multi‐spin systems hold great promise for applications in quantum information technology, artificial photosynthesis, as well as spin catalysis. The quartet state formation was scrutinised by femtosecond UV/Vis absorption and electron paramagnetic resonance spectroscopies, providing unique insight into the excited state reaction mechanism. Image design by Niklas Markloff, with contributions from Oliver Nolden. More information can be found in the Full Paper by S. Richert et al. on page 2683 .